2022
DOI: 10.1123/jpah.2022-0312
|View full text |Cite
|
Sign up to set email alerts
|

Recent Secular Trends in Child and Adolescent Physical Activity and Sedentary Behavior Internationally: Analyses of Active Healthy Kids Global Alliance Global Matrices 1.0 to 4.0

Abstract: Background: We examined recent global secular trends in 5 indicators of child and adolescent physical activity and sedentary behavior (Overall Physical Activity, Organized Sport and Physical Activity, Active Play, Active Transportation, and Sedentary Behavior) and 4 influences on these (Family and Peers, School, Community and Environment, and Government). Methods: Active Healthy Kids Global Alliance letter grades (A+ to F) were assigned numbers from 15 to 2, with 0 assigned for missing/incomplete grades. Trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…Our finding showing that Overall Physical Activity did not change over time is consistent with the results reported from Canada, 19 and a recent international paper 20 summarizing secular trends in Report Card Grades from Global Matrix 1.0–4.0. Similarly, findings from other previous studies also suggest that generally, physical activity has remained relatively stable, 21 although below the recommended levels 3 or has declined 22 among children and adolescents over time.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding showing that Overall Physical Activity did not change over time is consistent with the results reported from Canada, 19 and a recent international paper 20 summarizing secular trends in Report Card Grades from Global Matrix 1.0–4.0. Similarly, findings from other previous studies also suggest that generally, physical activity has remained relatively stable, 21 although below the recommended levels 3 or has declined 22 among children and adolescents over time.…”
Section: Discussionsupporting
confidence: 92%
“…This encouraging decrease of INC and deeper analysis providing a synthesis of international trends for behavioral and sources of influence grades that occurred from 2014 to 2022 are discussed in another article, which is part of the present special issue. 120 However, the remaining high prevalence of INC and the reliance on smaller regional surveys or studies in the absence of consistently nationally representative data highlight the need for advocacy to promote regular, national surveillance of PA in children and adolescents worldwide.…”
Section: Integrated Discussionmentioning
confidence: 99%
“…Health Summary of impact on behavioral indicators: It is too early to observe significant change in active behaviors in children, and any potential change in behavior (observed by grade temporal change for behavioral indicators) cannot be directly linked to the impact of the AHKGA Report Cards. However, our analysis of secular trends in report card grades between Global Matrices 1.0 and 4.0 24 found some modest international improvements in grades for both behavioral indicators and sources of influence indicators as well as modest improvements in surveillance of report card indicators, as indicated by a reduction in incomplete grades. In 2018, 89% of the report card leaders who participated in the Global Matrix 3.0 reported that in their opinion, the Global Matrix initiative was contributing to power the movement to get kids moving.…”
Section: Informing Decision Makingmentioning
confidence: 63%
“…This Brief Report is the first of 5 papers in this issue of the Journal of Physical Activity and Health that are focused on the findings from the Global Matrix 4.0. A detailed summary of the methods and main findings for the 10 report card indicators for all 57 participating jurisdictions, and geocultural clusters of countries, from the Global Matrix 4.0 is provided in the paper by Aubert et al 7 The main findings are then further dissected by Reilly et al, 24 who examine temporal changes in report card findings between and within countries that participated in combinations of the Global Matrices 1.0 to 4.0. Lee et al 25 explore geopolitical differences in grades with analyses considering economic freedom and climate culpability as well as specific national environmental indicators.…”
Section: Global Matrix 40 Series Papersmentioning
confidence: 99%